Exploring the nexus between social and environmental sustainability within EU organic agriculture: a systematic literature review - Magnano, Giulia; Falasconi, Luca; Giordano, Claudia (Frontiers in Sustainable Food Systems, 2024)
The European Union’s Farm-to-Fork Strategy and Green Deal underscore organic farming’s critical role in promoting sustainability and addressing socio-economic issues, including precarious, seasonal, and undeclared labor. The EU’s objective to have at least 25% of the agricultural land dedicated to organic farming by 2030 highlights the need for research into the social implications of organic practices, particularly concerning labor conditions, which remains largely unexplored. While existing literature often focuses on organic agriculture’s job creation potential, the specifics of labor conditions within this sector remain insufficiently examined. Limited attention has been paid to how private certification schemes shape labour processes, or to the effects of increased preventive measures on organic farmworkers’ workloads. This study conducts a systematic review of 41 articles to assess how labor issues are framed within the organic farming sector, identifying three main themes: 1. regulatory frameworks; 2. production practices; 3. farmworkers’ employment conditions. These themes are contextualized within the global agri-food value chain, demonstrating how organic agriculture is embedded in a globalized industry. The findings suggest that the social role of organic agriculture is often framed as an economic opportunity for farmers and rural communities or as a means of promoting rural development and increasing revenues through job creation. However, such perspectives risk overlooking the sector’s potential to improve labor conditions. The review reveals an urgent need for qualitative studies that explore the experiences of marginalized groups, including migrant and female workers, in organic farming. It advocates for future research that incorporates labor issues into policy discourse, aiming to enhance labor standards within organic certification schemes. Empirical research is therefore essential to deepening our understanding of the intersection between social and environmental sustainability, particularly in relation to the varied labor regimes present in organic agriculture. This work offers a foundational basis for future studies on the evolving relationship between organic agriculture and social sustainability in the context of the green transition.